Penguatan Ekonomi Di Tengah Badai Covid 19 - Ririn, Ririn Parmita; Fitriana, Fitriana; Nurhadi, Nurhadi (Jurnal Unicorn ADPERTISI, 2022)
The Covid-19 pandemic broke out in Palu City in March 2020, then the government implemented large-scale social reforms (PSBB) and the Government implemented level 4 updating of community activities (PPKM). economy, especially business in the city of Palu, which will narrow the space for small businesses to move, such as in the City Forest of Palu City. The aims of this research were to (1) change the way business actors in the Palu City Forest deal with enforcing government regulations during a pandemic and (2) change the way business actors in the Palu City Forest strengthen the economy in dealing with fluctuations in economic conditions due to COVID-19-19 so that stay stable. The results of the study show that (1) Follow government regulations regarding operating hours and health protocols, stock raw materials as needed, look for side businesses to increase capital and help the main business in the Palu City Forest. (2) Improving the entrepreneurial spirit through trainings held by the Government and the private sector, Strengthening product quality and product differentiation, Offering prices that are relatively stable as before the pandemic, Providing beautiful and comfortable places, and conducting promotions through social media.